Autoimmune Cytopenias and Dysregulated Immunophenotype Act as Warning Signs of Inborn Errors of Immunity: Results From a Prospective Study - Schiavo, Ebe; Martini, Beatrice; Attardi, Enrico; Consonni, Filippo; Ciullini Mannurita, Sara; Coniglio, Maria Luisa; Tellini, Marco; Chiocca, Elena; Fotzi, Ilaria; Luti, Laura; D’Alba, Irene; Veltroni, Marinella; et al. (Frontiers in Immunology, 2022)
Inborn errors of immunity (IEI) are genetic disorders characterized by a wide spectrum of clinical manifestations, ranging from increased susceptibility to infections to significant immune dysregulation. Among these, primary immune regulatory disorders (PIRDs) are mainly presenting with autoimmune manifestations, and autoimmune cytopenias (AICs) can be the first clinical sign. Significantly, AICs in patients with IEI often fail to respond to first-line therapy. In pediatric patients, autoimmune cytopenias can be red flags for IEI. However, for these cases precise indicators or parameters useful to suspect and screen for a hidden congenital immune defect are lacking. Therefore, we focused on chronic/refractory AIC patients to perform an extensive clinical evaluation and multiparametric flow cytometry analysis to select patients in whom PIRD was strongly suspected as candidates for genetic analysis. Key IEI-associated alterations causative of STAT3 GOF disease, IKAROS haploinsufficiency, activated PI3Kδ syndrome (APDS), Kabuki syndrome and autoimmune lymphoproliferative syndrome (ALPS) were identified. In this scenario, a dysregulated immunophenotype acted as a potential screening tool for an early IEI diagnosis, pivotal for appropriate clinical management and for the identification of new therapeutic targets.